Performance enhancement of linear active electronically scanned arrays by means of MbD-synthesized metalenses. Issue 8 (24th May 2018) - Salucci, M.; Oliveri, G.; Anselmi, N.; Gottardi, G.; Massa, A.
Abstract: The key problem of improving the radiation performances or enabling additive functionalities of linear active electronically scanned arrays ( AESA s), without increasing the number of radiating elements nor requiring a re-design of the radiators and/or the feeding network, is addressed by means of a suitably formulated Material-by-Design ( MbD ) approach. The quasi-conformal transformation optics ( QCTO ) technique and a customized source inversion ( SI ) strategy are jointly exploited to synthesize enhanced architectures, composed by a metamaterial lens and a tapered version of the original feeding network, able to match the radiation characteristics of significantly larger and/or different (from the original one) apertures. A set of representative benchmark results is reported to assess the effectiveness of the proposed MbD -designed architecture as well as to highlight the existing trade-off between achievable improvements and the complexity of the arising architectural solution.